Cognitive, psychological and social factors associated with older adults' mobility: a scoping review of self‐report and performance‐based measures. Issue 4 (9th May 2022) - Kalu, Michael E.; Bello‐Haas, Vanina Dal; Griffin, Meridith; Boamah, Sheila; Harris, Jocelyn; Zaide, Mashal; Rayner, Daniel; Khattab, Nura; Abrahim, Salma; Richardson, Tristan K.; Savatteri, Nicholas; Wang, Yimo; et al.
Abstract : Although many factors have been associated with mobility among older adults, there is paucity of research that explores the complexity of factors that influence mobility. This review aims to synthesise the available evidence for factors comprising the cognitive, psychological, and social mobility determinants and their associations with mobility self‐reported and performance‐based outcomes in older adults (60 years). We followed Arksey and O′Malley's five stages of a scoping review and searched PubMed, EMBASE, PsychINFO, Web of Science, AgeLine, Allied and Complementary Medicine Database, Cumulative Index to Nursing and Allied Health Literature and Sociological Abstract databases. Reviewers in pairs independently conducted title, abstract, full‐text screening and data extraction. We reported associations by analyses rather than articles because articles reported multiple associations for factors and several mobility outcomes. Associations were categorised as significantly positive, negative, or not significant. We included 183 peer‐reviewed articles published in 27 countries, most of which were cross‐sectional studies and conducted among community‐dwelling older adults. The 183 articles reported 630 analyses, of which 381 (60.5%) were significantly associated with mobility outcomes in the expected direction. For example, older adults with higher cognitive functioning such as better executive functioning had better mobility outcomes (e.g., faster gait speed), and those with poor psychological outcomes, such as depressive symptoms, or social outcomes such as reduced social network, had poorer mobility outcomes (e.g., slower gait speed) compared to their counterparts. Studies exploring the association between cognitive factors, personality (a psychological factor) and self‐reported mobility outcomes (e.g., walking for transportation or driving), and social factors and performance‐based mobility outcomes in older adults are limited. Understanding the additive relationships between cognitive, psychological, and social factors highlights the complexity of older adults' mobility across different forms of mobility, including independence, use of assistive devices, transportation, and driving.